Restrictive clauses (covenants) in bond contracts: empirical evidence in Chile - Araya, Alvaro; Islas, Gonzalo; Maquieira V., Carlos (Estudios de Administración, 2002)
Within financial literature aimed at analyzing agency issues, a particularly interesting aspect of it corresponds to the conflict that arises between stockholders and bondholders. There is a fair amount of literature that dissects the different manifestations or outcomes that such a conflict might generate, as well as the possible ways of solving these, one of which is the use of covenants in debt contracts. This paper presents a discussion in the main features of the stockholder-bondholder conflict, a description of the regulatory framework of bond issuance in Chile and a clinical assessment of the characteristics of the covenants used in Chile, from 1987 to 2000, specially emphasizing of certain specific clauses in the Chilean debt market. This paper shows that the covenants most widely used in the Chilean Market, are those related to the claim dilution problem (83% of the contracts restrict the either financial policy or the capital structure).